A study of customer's satisfaction towards Unit Trust Consultant (UTC) service quality / Dayang Noorazlinah Abang Noorzuki - Abang Noorzuki, Dayang Noorazlinah (2008)
Service sector is a growing and recently has become the most important sector in most countries around the world. In addition, many countries has shift their major economic based from agricultural and manufacturing sector to service sector (Voon Boo Ho and Karen Kueh, 2004). Service sector can be in many form and banking and investment industry is one major part of it. According to Huseyin Arasli (2005) in his research entitled Customer Service Quality in the Greek Cypriot Banking Industry, banking and financial industry is a most demand driven industry which constitute to an important part of service industry. However, service industry always be linked directly with customer satisfactions. Customer’s preferences and lifestyle can be in many forms, and better understanding toward their needs is a key to win their heart (Voon Boo Ho and Karen Kueh, 2004). In Unit Trust investment perspective, offering customers a service to persuade him or her to make investment also require a good understanding in customer service quality. According to a guideline from Securities Commission Malaysia, there are some guidelines for Unit Trust Consultant (UTC) to follow when dealing with customers under section 58(1) of CMSA, must be a holder of Capital Market Service License or must be a registered person to make sure they are the most eligible person to deal with customers especially providing a satisfying service quality. Unit Trust Consultant is a person that giving free consultation and advices to the customer to make investment. A Unit Trust Consultant (UTC) should possess a sense of responsibility, integrity and professionalism in dealing with unit trust fund and investor (Securities Commission Malaysia, 2008). Fulfilling the investors needs in providing information maybe different from one investor to another. The reason is because the investor came from a different background and definitely brings different expectation toward the UTC’s service (Piham and Taylor, 2000). In Malaysia, the role of unit trust fund in Bursa Malaysia is very important where it contributes to 19.91% of Net Asset Value (NAV) to Bursa in July 2012. The value has decrease from 20.31% in June 2012 and 20.61% in May 2012 (Federation of Investment Managers Malaysia, 2012).